Going with the flow an exploratory study on the coping mechanisms of parents and their compliance to the messages from their local government about flooding - Velasco, Dior Khristian P. 1990-; Zapanta, Jamaica A.
"The study aimed at looking into the coping mechanisms of parents in a flood-prone city and their compliance with the messages from barangay as well as from other sources of information regarding disaster management. The study was guided by the Health Belief Model, Protection Motivation theory, and Persuasion theory in order to gauge the behaviour change among individuals and the factors that influences such change. A qualitative approach was utilized in achieving the goals of the study. Three barangays in Marikina City were chosen to be the areas of study because of their susceptibility to flooding-Malanday, Nangka, and Tumana. Key informant interviews with barangay officials were done to identify the strategies they employ in disseminating information to their constituents. Focus interviews among parents were conducted to determine their coping mechanism based on the messages they receive from the local government. From the focus interviews, preparedness and safety were the common themes that emerged from the messages that the barangays communicate and the parents receive. The barangays employed several communication channels and materials in increasing the awareness of the people regarding disaster management. Besides the barangay, television was found to be the most used reference about typhoon updates. Parents in general follow the messages from the barangay when coping with flooding. Although most parents evacuate when advised by the barangay, there are a few who choose to stay in their houses because they feel confident with their personal gauge of the level of water. After the destruction of typhoon Ondoy in 2009, the barangay officials and parents learned to be more prepares and aware when there are disasters, thus a change in behaviour was observed."